Australian police perceptions of women's police stations. (2nd November 2022) - Rodgers, Jess; Carrington, Kerry; Ryan, Vanessa
ABSTRACT: Women's police stations that are designed to receive victims of gender-based violence first emerged in Latin America in the 1980s. In Argentina, these stations have unique aspects like multidisciplinary staffing that could guide responses elsewhere. Police responses to domestic and family violence (DFV) in Australia have continually failed victims and require much improvement. Responses combining police and other services are not completely alien to Australia, and are not too dissimilar from women's police stations. We undertook a survey of Australian police (n = 78) to assess which aspects of Argentina's stations could inform new approaches to DFV policing. Our survey finds that Australian police support some aspects of this approach to policing DFV, such as multidisciplinary stations (74%). There was significantly less support for stations staffed predominantly by women (19%). Combined with review of evaluations of Australian co-locational responses, research implications for practice suggest a broader trial of co-locational responses in Australia.